Theoretical and practical aspects of the efficiency of application of mineral fertilizers encapsulated with polyethylene terephthalate - Synelnikov, Serhiy; Malovanyy, Myroslav; Nahurskyy, Oleh; Luchyt, Liubov; Petrushka, Kateryna; Tymchuk, Ivan; Stokaliuko, Oleh (Видавництво Львівської політехніки, 2020)
The environmental impact of residual mineral fertilizers not utilized by plants is analyzed. It is shown that this negative effect extends to all elements of the environment: soil, atmosphere, hydrosphere. The perspective of the application of encapsulated mineral fertilizers that allow prolonged release of plant nutrients is outlined. The appliccation of modified polyethylene terephthalate (PETF) as a capsule-forming material for encapsulated mineral fertilizers is proposed. PET modification and fertilizer encapsulation technologies have been tested. The dynamics of the release of nutrients from fertilizers encapsulated by PET has been studied. The kinetics of watercress salad growth with the use of granular and encapsulated fertilizers has been investigated.
Keywords: granulated mineral fertilizers; encapsulated mineral fertilizers; environment; nutrients; polyethylene terephthalate; release